2016
DOI: 10.3847/0004-637x/822/2/94
|View full text |Cite
|
Sign up to set email alerts
|

VOYAGER OBSERVATIONS OF MAGNETIC WAVES DUE TO NEWBORN INTERSTELLAR PICKUP IONS: 2–6 au

Abstract: We report observations by the Voyager 1 and 2 spacecraft of low-frequency magnetic waves excited by newborn interstellar pickup ions H + and He + during 1978-1979 when the spacecraft were in the range from 2 to 6.3 au. The waves have the expected association with the cyclotron frequency of the source ions, are left-hand polarized in the spacecraft frame, and have minimum variance directions that are quasi-parallel to the local mean magnetic field. There is one exception to this in that one wave event that is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 98 publications
2
26
0
Order By: Relevance
“…EMWs have been observed extensively in many plasma environments, such as the magnetosphere (Russell & Blancocano 2007;Meredith et al 2014;Sugiyama et al 2015;Lee & Lee 2016), the magnetotail (Nakagawa et al 2018), the Earth's magnetosheath (Denton et al 1994(Denton et al , 1998Song et al 1994), and the solar wind (Jian et al 2009(Jian et al , 2010(Jian et al , 2014Aggarwal et al 2016;Gary et al 2016;Wicks et al 2016;Zhao et al 2017a). In the solar wind, interplanetary magnetic clouds (IMCs) are the most important subset of CMEs erupted from the Sun and have a large-scale magnetic flux rope structure.…”
Section: Introductionmentioning
confidence: 99%
“…EMWs have been observed extensively in many plasma environments, such as the magnetosphere (Russell & Blancocano 2007;Meredith et al 2014;Sugiyama et al 2015;Lee & Lee 2016), the magnetotail (Nakagawa et al 2018), the Earth's magnetosheath (Denton et al 1994(Denton et al , 1998Song et al 1994), and the solar wind (Jian et al 2009(Jian et al , 2010(Jian et al , 2014Aggarwal et al 2016;Gary et al 2016;Wicks et al 2016;Zhao et al 2017a). In the solar wind, interplanetary magnetic clouds (IMCs) are the most important subset of CMEs erupted from the Sun and have a large-scale magnetic flux rope structure.…”
Section: Introductionmentioning
confidence: 99%
“…From theoretical (see, e.g., Lee & Ip 1987;Williams & Zank 1994;Zank 1999;Isenberg 2005), observational (e.g., Joyce et al 2010;Cannon et al 2014aCannon et al , 2014bCannon et al , 2017Aggarwal et al 2016), and numerical (Hellinger & Trávníček 2016) studies we now know that the continual production of pickup protons from incoming interstellar neutral hydrogen by means of photoionization or charge exchange with solar wind protons (see, e.g., Scherer et al 2014) leads to the formation of Alfvén cyclotron waves that in turn lead to an enhancement in the wave frequency spectra at large frequencies. In situ observations of such enhancements have, however, only rarely been seen (e.g., Cannon et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Our recent efforts to continue this study revealed to us a significant error in Table 3 of the published article. Here we correct that table for the sake of future work by ourselves and others.Past analyses of magnetic waves due to newborn interstellar pickup ions observed in interplanetary space have revealed that the waves are most often observed when the background fluctuation levels are low (Cannon et al 2014;Aggarwal et al 2016;Fisher et al 2016). Our recent report of two such wave events observed by the Voyager 2 spacecraft on DOYs 172-174 of 1989 when the spacecraft was at 29.6 au, 3°.…”
mentioning
confidence: 99%